Attachment, behavior problems and interventions - Hutchings, Judy; Williams, Margiad E.; Leijten, Patty (Frontiers in Child and Adolescent Psychiatry, 2023)
This paper puts forward an explanation for the frequent co-occurrence of attachment and behavior problems in children and the implications of this for interventions; presents preliminary evidence that some behaviorally based parenting programs reduce child behavior problems through two separate, but mutually reinforcing, processes - improved attachment relationships and increased parental use of behavior management techniques; and suggests next steps for the field to improve outcomes for those children who, without interventions that addresses both relationship building and behavior management, are at risk of significant long-term difficulties.